2020
DOI: 10.1093/plphys/kiaa039
|View full text |Cite
|
Sign up to set email alerts
|

Tri-SUS: a yeast split-ubiquitin assay to examine protein interactions governed by a third binding partner

Abstract: The yeast Tri-SUS system can be used to study tripartite protein–protein interactions between bait and prey protein pairs by modulation of expression of their binding partner

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…How might the SNARE coordinate the association with both aquaporins and plasma membrane H + ‐ATPases? One clue comes from additional yeast Tri‐SUS analysis (Zhang et al., 2021) which showed that PIP2;1 and H + ‐ATPase AHA1 are likely to occur in a complex with the SNARE SYP132 (Figure S4). The Tri‐SUS system detects tripartite bait and prey interactions involving a third methionine‐repressible partner protein (Figure S4a).…”
Section: Resultsmentioning
confidence: 99%
“…How might the SNARE coordinate the association with both aquaporins and plasma membrane H + ‐ATPases? One clue comes from additional yeast Tri‐SUS analysis (Zhang et al., 2021) which showed that PIP2;1 and H + ‐ATPase AHA1 are likely to occur in a complex with the SNARE SYP132 (Figure S4). The Tri‐SUS system detects tripartite bait and prey interactions involving a third methionine‐repressible partner protein (Figure S4a).…”
Section: Resultsmentioning
confidence: 99%